The REACT-Based Contextual Learning Model And Mastering The Concept Of Physics In High School Students - Abdul Hamid (Universitas Syiah Kuala, 2021)
This study aims to determine the effect of the REACT-based contextual learning model on the mastery of physics concepts in high school students. This study used a Quasi Experimental research model with a pretest-posttest control group design. The study population was all students of class XI MIA SMA Negeri Samadua, South Aceh Regency which consisted of two classes. Both classes were used as research samples by forming an experimental group and a control group. The experimental group is a class that uses a REACT-based contextual learning model in physics learning, while the control group is a class that uses a conventional learning model through the lecture method. The instruments used were RPP, LKPD and test questions. The pretest and posttest in this study were used to measure the students' initial and final abilities in physics. The data analysis technique used is the t-test with a significance level of 5%. The results of hypothesis testing obtained tcount (2.13) ttable (1.68), meaning that Ho is rejected and Ha is accepted. These results interpreted that there was a significant influence on the REACT-based contextual learning model on the mastery of physics concepts for students of class XI MIA SMA Samadua, South Aceh Regency.